Analisis Solvabilitas dan Profitabilitas dalam Mengukur Kinerja Keuangan PT Pelabuhan Tanjung Priok Periode 2017-2021 - Sugih, Sugiharti (Information Technology and Science (ITScience), 2021)
The purpose of this study is to analyze the Solvency seen by Debt to Total Asset Ratio, and Debt To Total Equity as well as Profitability seen from Profit Margin, Return On Asset, and Return On Equity and to find out the extent to which the company's assets are financed with debt. Measuring Financial Performance and analyzing it with Solvency and Profitability based on cashmere opinions. This type of research uses qualitative research based on assumptions, data collection, and research design is flexible or subject to change. The data sources in this study are Primary and documentation and data collection techniques by means of observation, documents, and triangulation. The data analysis procedure is based on the opinion of Kasmir to measure and analyze the financial statements of Tanjung Priok Port. To check the validity of the data researchers use Triangulation, Discussion, and Membercheck. The results of the study in measuring the Financial Performance of PT Tanjung Priok Port are seen from Solvency and Profitability, and based on the opinion of Kasmir for the 2014-2018 period which states that